Case report: Concurrent malignant triton tumor and relapsed pituitary adenoma in the sellar region - Wang, Jinchao; Yao, Zhigang; Xu, Shangchen; Liu, Bin (Frontiers in Surgery, 2023)
Malignant triton tumor (MTT) is a rare kind of malignant peripheral nerve sheath tumors, histologically characterized by rhabdomyoblastic differentiation. There are limited reports of MTT occurring in the intracranial area. The treatment modality consisting of total surgical resection plus post-operative radiotherapy is generally accepted. However, even with optimal treatment, most patients will die within a few months. We report a 71-year-old man with a history of pituitary adenoma, who underwent surgical treatment and postoperative gamma knife therapy. Magnetic resonance imaging (MRI) of the brain revealed a mass with two distinctive components in the sellar area. Postoperative pathology found that the lesion consisted of a MTT and a relapsed pituitary adenoma. The present case is the first report of MTT that occurred in the sellar area. It is also the first case of intracranial MTT with other concurrent tumors (relapsed pituitary tumors). Meanwhile, this case has a clear history of radiation therapy, suggesting that the occurrence of MTT may be related to radiation.